INFORMATION TECHNOLOGIES IN IMPROVING ENERGY EFFICIENCY OF ELECTRIC MACHINES: Array - Daleka, V.; Kulbashna, N.; Kuznetsov, A. (Municipal economy of cities. Series: «Economy science», 2020)
The article provides results of research and suggestions for increasing energy efficiency of electric machines based of informational technologies in programming environment “КОМПАС-3D”. The article shows the relevance of resource saving for transport field where material, energetic, financial and human resources are being extensively used. Also, according to the statistical data almost 95% of electricity used by enterprises are being used to power transportation itself, hence power is used solemnly by electric vehicles – traction engines and auxiliary engines. Based on the analysis of research and their publications methods of increasing electric machines’ energy efficiency were discovered. Usage of methodology of designing and manufacturing electric machines based on CAD/CAM systems gives ability to forecast their energy efficiency and solve a problem of resource storage, quality and competitiveness. Development of resource-efficient electric engine is a process of finding optimal parameters or structure. A choice of optimal engine structure lies in choosing design of each individual element, quantity of elements and relations between them, in defining spatial distribution of the elements. Built-in parameters of engine make it possible to conduct further development without using of mathematical apparatus, manufacturing engines of different configurations and calculation of technical and economical indicators, which evaluate efficiency of given solutions. On the example of the traction motor of the trolleybus the dependences of SEC on its geometrical parameters, properties of magnetic materials, power of the vehicle, and also speed of movement of the vehicle are resulted. The expediency of solving resource saving issues during the whole design process is shown.